(untitled) (Raparin Journal of Humanities (RJH), 2020)
Teaching material is considered a crucial element to the success of student achievement. This study aims to assess the effectiveness of teaching materials of translation courses offered to third- and -fourth year in the Departments of English from the students’ perceptions. To achieve this, a questionnaire is used for data collection. This questionnaire is administered to (120) fourth-year students enrolled in the respective Departments of English of three Kurdistan Universities; (40) students from the University of Sulaimani, (40) students from Salahaddin University-Erbil, and (40) students from the University of Duhok, to find out the extent to which students are satisfied with the current translation materials offered in their departments. The data of the study are analyzed via (SPSS) using descriptive statistics. Accordingly, findings have shown that the students are unsatisfied with many aspects of the translation teaching materials, such as a lack of balance among translation theories, methods, procedures, and the text types. Additionally, little attention is given to the cultural aspects in raising students’ cultural awareness, and there is a lack of coherence between the translation materials of third- and fourth-year. Thus, a need for developing textbooks for translation courses in the Departments of English is recommended.